PENGARUH KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN STRUKTUR ASSET TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahmi, Auliya; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the Effect of Institutional Ownership, Profitability and Asset Structure on Debt Policy on Property and Real Estate Companies Listed on the Indonesia Stock Exchange. The ratio used in measuring Institutional Ownership as an independent variable is INST. The ratio used in measuring Profitability is Return on Investment (ROI) and Return on Equity (ROE). The ratio used in measuring Asset Structure is AST. Meanwhile, the ratio used to measure the Debt Policy as the dependent variable is the Debt to Equity Ratio (DER). The method used to observe the effect of institutional ownership, profitability and asset structure on debt policy is to use simple linear regression and multiple linear regression. The data used in this study are secondary data in the form of financial reports and annual reports of annual reports. The data is listed on the Indonesia Stock Exchange for 5 years from the period 2012-2016. Sampling is done by purposive sampling, which is used is 19 companies. Data analysis using simple linear regression analysis, multiple linear regression, t test, f test, and determination test coefficient, using the SPSS 23 program. The results of the analysis show that the institutional ownership variables have a significant and negative effect on Property and Real Estate debt policies listed on the IDX, the profitability variable does not significantly influence Property and Real Estate debt policies listed on the IDX and asset structure variables have a negative and significant effect on policy Property and Real Estate debt listed on the IDX. The results of the study simultaneously indicate that there are effects of institutional ownership, profitability and asset structure variables on the debt policies of Property and Real Estate companies listed on the Indonesia Stock Exchange.Keywords: institutional ownership, profitability, asset structure, and debt policy